Edukasi dan Pelatihan Pembuatan Infusa Herbal dari Tanaman TOGA (Tanaman Obat Keluarga) pada Siswa/I SMK Taruna Mandiri Pekanbaru - Sisri Novrita; Ratna Kurniati; Liza Tri Putri; Tiara Rahmadani Siregar; Fahira Dwi Anjani; Rara Eka Putri; M Arif Febrianta; Ramadhani Arifah (PPNI UNIMMAN, 2024)
Drinks made from natural ingredients, especially those from family plants, have health benefits for improving the immune system in the body. Processing of family medicinal plants (TOGA) has different benefits such as turmeric, ginger, galangal, lemongrass, lime and honey. When combined, herbal plants provide more comprehensive health benefits compared to consuming one type of herbal alone. It is hoped that the combination can provide healing benefits for various diseases by processing it into herbal drinks such as infused water. Infusion is a liquid preparation made by extracting vegetable simplicia such as ginger, turmeric, galangal, lemongrass, honey and lime with water at a temperature of 90˚C for 15 minutes while stirring occasionally. Socialization regarding the use of infused water needs to be carried out among the public, such as teenagers at high school level. With the existence of the KKN program